Jalons pour une réflexion sur l'orientation professionelle de l'avenir - Laflamme, Claude (Canadian Journal of Counselling and Psychotherapy, 2011)
Science in general and human sciences in particular are dependent, to a large extent, on the economic situation for their orientations and their goals. It follows that the orientations and goals, in the domain of vocational choice, are subject to questioning. Consequently, those working in the field are asked to take into consideration the actual economic and social situation.